2009
DOI: 10.1007/s12274-009-9061-4
|View full text |Cite
|
Sign up to set email alerts
|

Core-shell Au-Ag nanoparticles in dielectric nanocomposites with plasmon-enhanced fluorescence: A new paradigm in antimony glasses

Abstract: The nano era demands the synthesis of new nanostructured materials, if possible by simplified techniques, with remarkable properties and versatile applications. Here, we demonstrate a new single-step reproducible melt-quench methodology to fabricate core-shell bimetallic (Au 0 Ag 0 ) nanoparticles (28 89 nm) embedded glasses (dielectrics) by the use of a new reducing glass matrix, K 2 O B 2 O 3 Sb 2 O 3 (KBS) without applying any external reducing agent or multiple processing steps. The surface plasmon resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 37 publications
3
36
0
1
Order By: Relevance
“…However, design of facile and general strategies for the synthesis of other intermetallics and alloys with high surface areas still remains a great challenge. Undoubtedly, the emergence and development of nanoscience and nanotechnology offer new opportunities in this area [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, design of facile and general strategies for the synthesis of other intermetallics and alloys with high surface areas still remains a great challenge. Undoubtedly, the emergence and development of nanoscience and nanotechnology offer new opportunities in this area [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, design of facile and general strategies for the synthesis of other intermetallics and alloys with high surface areas still remains a great challenge. Undoubtedly, the emergence and development of nanoscience and nanotechnology offer new opportunities in this area [14][15][16][17][18].Recently, we developed a general strategy for the synthesis of various nanocrystals, whereby noble metal ions can be reduced to monodisperse noble metal nanocrystals by a mixture of ethanol and linoleic acid [19]. However, attempts to synthesize intermetallics and alloys of noble and non-noble metals (e.g., FePt, NiPt, and CoPd) with this strategy were unsuccessful, mainly due to the low reducing power of ethanol and linoleic acid.…”
mentioning
confidence: 99%
“…To understand the dynamics of the formation of alloy NPs, UV-Vis spectra were recorded for a solution with equal concentration but varying molar ratio of both metal precursors. It is reported that in case of alloy NPs, plasmon band shifts toward another one (either blue or red) if the molar ratio of one increase by keeping constant of another precursors [10]. The mono-metallic PEC-AuNPs showed characteristic peak at 523 nm (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…HRTEM analysis (inset of Fig. 2e) shows clear lattice fringes of the NPs with an interplanar distance with lattice fringes 0.24 nm corresponding to (111) plane, which indicates that the PECs supported NPs are well crystalline [10]. To understand the dynamics of the formation of alloy NPs, UV-Vis spectra were recorded for a solution with equal concentration but varying molar ratio of both metal precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Metal alloy nanoparticles (NPs) such as Au-Ag alloy NPs have received considerable attention in recent years because of their unique properties and potential applications in catalysis, photonics, optoelectronics, biological tagging and pharmaceutical applications [1][2][3]. The performance of Au-Ag alloy NPs depends critically on their size, shape and composition [4].…”
Section: Introductionmentioning
confidence: 99%